2014
DOI: 10.4040/jkan.2014.44.6.672
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Coaching Program on Comprehensive Lifestyle Modification for Women with Gestational Diabetes Mellitus

Abstract: Purpose: The purpose of this study was to investigate the effects of using a Coaching Program on Comprehensive Lifestyle Modification with pregnant women who have gestational diabetes. Methods: The research design for this study was a non-equivalent control group quasi-experimental study. Pregnant women with gestational diabetes were recruited from D women's hospital located in Gyeonggi Province from April to October, 2013. Participants in this study were 34 for the control group and 34 for the experimental gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 19 publications
0
60
0
Order By: Relevance
“…In the prospective study by Levy-Shiff et al[66], higher levels of patient-reported support from medical staff were associated with lower levels of depression in women with pre-existing diabetes ( P < 0.01). Similarly, in the prospective study by Ko et al[45], women with GDM who participated in a 4-week educational coaching program had a greater decrease in depression scores than those who did not participate. In the prospective study by Ragland et al[54], only 19% of women with concurrent DIP (any type) and depression (Beck Depression Inventory score > 13) were receiving treatment for depression.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…In the prospective study by Levy-Shiff et al[66], higher levels of patient-reported support from medical staff were associated with lower levels of depression in women with pre-existing diabetes ( P < 0.01). Similarly, in the prospective study by Ko et al[45], women with GDM who participated in a 4-week educational coaching program had a greater decrease in depression scores than those who did not participate. In the prospective study by Ragland et al[54], only 19% of women with concurrent DIP (any type) and depression (Beck Depression Inventory score > 13) were receiving treatment for depression.…”
Section: Resultsmentioning
confidence: 82%
“…Overall, 48 publications were included in this review (Figure 1, Table 1, Table 2, Table 3, Supplementary Table 1). Of these, 30 described prospective observational studies[20,21,23,24,26,27,29-31,34,35,37,38,41,43-45,47-49,51,54,57,58,60-62,65-67], 15 described retrospective observational studies[22,25,28,32,39,40,42,46,50,53,55,56,59,63,64], and three described randomized controlled trials (RCTs)[33,36,52], two of which reported only baseline data[36,52]. Two publications described the same study, but reported different subgroup analyses[23,29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The awareness of its risk factors plays a key role in the prevention of the complications [11,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%